Morphologies and potential roles of telocytes in nervous tissue - Xu Zhang; Ping Lu; Xiaorong Shen (Wiley, 2023)
Abstract Structurally similar cells have been found and termed telocytes (TCs) since the first characterisation of interstitial Cajal‐like cells in 1911. TCs are a novel and peculiar interstitial cell type with a small cellular body, markedly long cell processes named telopodes and a wide distribution in numerous tissues throughout the body. Besides specific morphological characteristics and immunohistochemical profiles, TCs build three‐dimensional mixed networks through homocellular (connection to each other) and/or heterocellular contacts (connection with other cell types), interaction with extracellular matrix and their vicinity to nerve endings, and thus might play, as part of an integrated system, roles in maintaining organ/tissue function. In this mini‐review, we summarise physical properties, general characteristics and distribution of TCs in diverse organs and tissues, focusing on their potential functions in nervous tissue and current challenges in investigating TCs as a distinct cell type.